Pathogenicity of field strain of fowl aviadenovirus serotype 11 isolated from chickens with inclusion body hepatitis in Morocco. - Samira Abghour; Mohamed Mouahid; Sami Darkaoui; Jaouad Berrada; Khalil Zro; Faouzi Kichou (PLoS ONE, 2021)
Outbreaks of inclusion body hepatitis have emerged in Morocco since 2013 and has resulted in significant economic losses to poultry farms. Three isolates of the causative virus, Fowl adenonovirus (FAdV)were characterized from chickens with IBH, but their pathogenicity has never been investigated. In this work, the pathogenicity of an isolate FAdV 11 (MOR300315 strain) was evaluated by inoculating a group of 40 SPF chickens at 3 days of age by oral route. A group of 40 chicks injected with phosphate-buffered saline solution was used as a control group. The infected chickens showed decreased weight gain from 3dpi. Necropsy displayed pallor and enlargement in liver, swelling and slight hemorrhage in kidney and spleen at 6 dpi. Histopathological changes were mainly characterized by severe and extensive hepatic necrosis associated with the presence of basophilic intra-nuclear inclusion bodies within hepatocytes. The FAdV was reisolated in chicken embryo fibroblast cell culture from liver tissue homogenate of infected chicken from 3 to 6 dpi. Viral DNA was detected by PCR in liver, kidney, spleen and cloacal swabs from 3 to 13 dpi. Antibody response against inoculated FAdV was appeared from 9 dpi. These results confirmed that the FAdV 11 strain is pathogenic in chicken. This study is the first experimental infection of FAdV 11 in chicken in Morocco, which increase our understanding of its pathogenicity in chickens and indicate that preventive measures against FAdV infection in poultry farms should be implemented in Morocco.